ILUX 2015: Shining like a cartoon - Ribeiro, Daniel (2015)
An image is an excellent tool for the communication of ideas/subjects in diverse situations, namely when the memorization of the contents is one of the goals. Moreover, as the mankind is mainly visual in what concerns to the learning style, the recourse to a visual tool (photo, illustration, scheme, cartoon, ...) seems to be a good strategy. When it comes to the cartoon technique, and because of the combination of virtually no text and the visual elements spiced with humoristic details, it catches the eye, sparks the good mood, and frequently, awakes the curiosity to learn more. Taking all this in consideration, the authors of the present work have been developing and applying the cartoon technique, during the last few years, to the communication of science contents to several particular publics. Light is present in all mankind activities, from everyday life to the cutting edge high- tech scenarios. Additionally, the United Nations proclaimed 2015 as the International Year of Light and Light-Based Technologies (IYL 2015). iLUX 2015 is a gallery of cartoons, created in the scope of the IYL 2015, as a work in progress (WIP) project through the year. Each cartoon covers a science content related to Biology, Physics or Chemistry and centered in light. The subject is approached in a visual, accessible and appealing way to a general public. Some topics covered are the bioluminescence of fireflies, the light pollution and environmental concerns, the phototropism, the shadow and sundials, the light refraction, the light separation and the rainbow formation, the fireworks composition, the sun and vitamin D production in skin, the incandescent lamps and LEDs in what concerns to energy efficiency, the evolution of stars, to name just a few. The iLUX 2015 gallery can be seen as a virtual resource in several locations (CBMA webpage and STOL and AIL 2015 pages in Facebook). Apart from this, the gallery will be printed and exhibited during the European Researchers Night 2015, as well as during the present International Conference of Communication and Light